Protestant pilgrimage to Jerusalem: preparations for the kingdom of God in apocalyptic rhetoric strategy - Maria Leppäkari (Scripta Instituti Donneriani Aboensis, 2003)
The vast majority of sacred shrines and holy sites host pilgrims united by strong degrees of cultural homogeneity. But Jerusalem differs on this point- it draws pilgrims from a vast multitude of nations and cultural traditions since the city is considered holy by three major religious traditions: Judaism, Christianity and Islam. The representatives of these traditions go partly to different places at different times where they are engaged in different forms of worship. Often these visits are marked by clashes at the holy places. The notion of Jerusalem in religious belief is constructed by the transmission of various representations concerned with the image of the city. For Western Christianity today, Jerusalem is not only important because of the things which Jesus of Nazareth, according to the tradition, did there. For many Christians Jerusalem is vitally important because of the apocalyptic promise Jesus left his followers with: I'll be back! Therefore, the position of Jerusalem in the religious end-time play is crucial, since apocalyptic representations of the New Jerusalem motivate contemporary believers to make a pilgrimage to Jerusalem, and to partake actively in political disputes about the Israeli—Palestinian conflict.